2006
DOI: 10.1177/0091270005283280
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology of Multiple Doses of Lasofoxifene in Postmenopausal Women

Abstract: Lasofoxifene, a next-generation selective estrogen receptor modulator, is undergoing phase 3 clinical development for osteoporosis. This study evaluated daily lasofoxifene for 14 days in healthy postmenopausal women. A loading dose of 5 times the daily dose was followed by daily doses of 0.01 mg (n = 8), 0.03 mg (n =8), 0.1 mg(n = 16), 0.3 mg (n =9), 1 mg (n = 8), or placebo (n = 16). Samples were collected for pharmacokinetic and pharmacodynamic assessments. Lasofoxifene was well tolerated; study drug-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…As stated in the FDA Guidance for Industry on Drug Metabolism [21], it is necessary to determine the metabolic pathways and routes of elimination of new drugs to ensure their safety and to understand the potential for drug-drug interactions. Lasofoxifene elimination is slow, with a t 1/2 of 5-6 days [6]. Renal excretion of unchanged lasofoxifene accounts for only 2% of the dose, whereas metabolism, including oxidation and conjugation pathways, appears to play a more important role.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As stated in the FDA Guidance for Industry on Drug Metabolism [21], it is necessary to determine the metabolic pathways and routes of elimination of new drugs to ensure their safety and to understand the potential for drug-drug interactions. Lasofoxifene elimination is slow, with a t 1/2 of 5-6 days [6]. Renal excretion of unchanged lasofoxifene accounts for only 2% of the dose, whereas metabolism, including oxidation and conjugation pathways, appears to play a more important role.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, lasofoxifene was shown not to have detrimental effects on the endometrium, which is a significant advantage over oestrogen [5]. Multiple doses ranging from 0.01 to 1 mg daily were administered in postmenopausal women [6]. Lasofoxifene pharmacokinetics were linear and the treatments were well tolerated [6].…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations